Chloride intracellular channel 1 functions in endothelial cell growth and migration - Tung, Jennifer J; Kitajewski, Jan (Vascular Cell, 2010)
Abstract Background Little is known about the role of CLIC1 in endothelium. These studies investigate CLIC1 as a regulator of angiogenesis by in vitro techniques that mimic individual steps in the angiogenic process. Methods Using shRNA against clic1 , we determined the role of CLIC1 in primary human endothelial cell behavior. Results Here, we report that reduced CLIC1 expression caused a reduction in endothelial migration, cell growth, branching morphogenesis, capillary-like network formation, and capillary-like sprouting. FACS analysis showed that CLIC1 plays a role in regulating the cell surface expression of various integrins that function in angiogenesis including β1 and α3 subunits, as well as αVβ3 and αVβ5. Conclusions Together, these results indicate that CLIC1 is required for multiple steps of in vitro angiogenesis and plays a role in regulating integrin cell surface expression.